A multi-type multi-occurrence hazard lifecycle cost analysis framework for infrastructure management decision making. (15th July 2018) - Fereshtehnejad, Ehsan; Shafieezadeh, Abdollah
Highlights: Infrastructures are vulnerable against multiple occurrences of multiple types of hazards. Their vulnerability increases if they are not repaired by the time of next hazards. The proposed framework incorporates effects of prior damage and repair times on future performance of systems. It employs a recursive algorithm to effectively incorporate uncertainties from various sources. Impacts of considering prior damage and repair time variations are shown for a realistic bridge. Abstract: Infrastructure systems, especially in hazard-prone regions, may face multiple occurrences of multiple types of hazards during their lifetime. The type and intensity of the hazards and impacts on systems can vary from one event to another. An important factor that has yet to be properly addressed in natural hazard loss estimation models is the impact of damage induced by various types of prior events on the increased vulnerability of systems against various types of potential future hazards. This paper presents a new hazard lifecycle cost analysis framework that addresses this gap and accounts for effects of incomplete repairs of damage conditions induced by prior natural hazards on the future hazard performance of systems. Considering that the space of scenarios for multi-hazard occurrences and the impacts over the lifetime of infrastructure systems is significantly large, a recursive algorithm is proposed to efficiently determine the lifecycle cost of the system. This framework is applied to a realistic bridge exposed to flood and earthquake hazards to determine the optimal retrofit plan that reduces the overall lifecycle cost of the bridge. Results show the significance of considering different damage types induced by multiple types of hazards and repair time variations for lifecycle cost analysis of infrastructure systems.